(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2017)
The community engagement strategies of Tuberculosis programmes prioritized on increasing case finding. There are limited evidences on - what an empowered community can do for Tuberculosis care? An innovative community empowerment model was developed and implemented in districts of India as “District Tuberculosis Forum” (DTF) under Project Axshya to engage and empower community. The paper here describes the contributions made by empowered forum members. We collected quantitative data from 77 districts for activities conducted during June 2013 to July 2014. The analysis is focused on activities conducted within patient centric, community and programme centric approaches. Empowered community members sensitized over 9000 TB patients on their rights and responsibilities and generated resources to support nearly 700 patients. The model is promising with key stakeholders at district level coming forward to get involved in activities supporting Tuberculosis prevention and care with an aim to END –TB. SAARC L TUBER DIS HIV/AIDS, 2016;XIII(1), page: 39-42